A Study on Reconciliation of Post-War Peacebuilding in Sri Lanka. - Wakkumbura, Menik; Wijegoonawardana, Nirmali (My University, 2017)
Since the end of war in Sri Lanka in 2009, the landscape of the reconciliation process has come under critical debate. In response, the Sri Lankan government efforts in reconciliation and all other types of efforts are seemingly on increase for achieving peace. In this light, the paper critically examines both practice and theoretical development of how ‘justice’ in the reconciliation can impact on ‘positive peace’ as a greater peacebuilding effort evident to be useful in post-war Sri Lanka. It is debated how reconciliation experienced at all societal layers have considered justice as a prerequisite for successful outcomes. Therefore, given the empirical evidence, the paper has prioritized how social justice, removal of cultural barriers and consideration on a wider scope of human rights, regarded in justice become a core contributory factor of Sri Lanka`s reconciliation. And these attempts leads for structural changes using of different peacebuilding approaches i.e., national and grassroots. However, in Sri Lanka reconciliation has experienced a number of vital challenges. These challenges are the complex nature of the process, broken consensus on justice among people, politicized decision-making, policy gaps and many more. While investigating important empirical findings about the reconciliation process in Sri Lanka, the paper critically examines the use of different reconciliation approaches and how far “justice” has been criticized within the implementation. The study has utilized content analysis and a descriptive narrative to examine the research problem. The discussion arrives at a conclusion of using of both national and grassroots peacebuilding approaches and serious emphasis on justice would let reconciliation to be closer in achieving positive peace. The discussion also reveals the complexities of such achievements unless addressed on conditions i.e., lack of economic reconstruction, social and emotional competencies, trust, healing and forgiveness
Keywords: Reconciliation, Justice, Peacebuilding, Positive Peace, Sri Lanka